LEARNING ENGLISH THROUGH POP CULTURE - Karimova Nigina Sunnatillo qizi (Web of Journals Publishing, 2025)
This article explores the influence of pop culture on the process of learning the English language. Pop culture is a broad concept that encompasses various elements of mass media, including music, movies, TV series, animation, and social media, making it a natural, convenient, and enjoyable tool for language learning. This study examines the benefits of learning English through pop culture, such as increasing interest in the language, expanding vocabulary, and improving communication skills. Additionally, the article discusses the limitations of this approach and considers its potential drawbacks or challenges in ensuring effective language acquisition.
Keywords: Pop culture and language learning, English language education, motivation, audiovisual content, authentic materials, learning in a natural language environment.